Cross‐Sectional Versus Panel Income Approaches: Analyzing Income Distribution Changes for the Case of Mexico. (5th October 2016) - Duval‐Hernández, Robert; Fields, Gary S.; Jakubson, George H.
Abstract : In this paper we reconcile, both theoretically and empirically, changes in cross‐sectional inequality with patterns of panel income changes during periods of economic growth and decline. Using panel earnings data from Mexico, we find that the panel changes are convergent in almost every period, the reason being that a large number of individuals experience small convergent earnings changes while a small number of individuals experience large and convergent earnings changes. We examine what accounts for the inequality of log‐earnings at a point in time and for the inequality of the log of earnings averaged over five quarters. We find that the equalization brought about by panel earnings changes is mainly associated with changes in employment status and in sector of employment and not by personal characteristics such as schooling, age, and gender.